Two new species of Pachyseius Berlese (Acari: Pachylaelapidae) from Turkey, with a key to the world species - Özbek Hasan Hüseyi̇n; Halliday, Bruce (Zootaxa, 2014)
The genus Pachyseius Berlese, 1910 (Acari: Pachylaelapidae) is reported from Turkey for the first time. Pachyseius siranensis sp. nov. and Pachyseius masani sp. nov. are described from females collected from litter and moss in north-eastern Turkey. A world-wide key to the species of Pachyseius is provided. The number of setae on the ventri-anal shield appears to be variable within some species in this genus. Some species of Pachyseius show reductions in chaetotaxy on tarsi III and IV.